Disentangling privacy in smart homes - Kraemer, MJ; Flechais, I (2018)
Researching Privacy in Smart Homes where society and technology overlap appears promising. Our research uses an Contextual Integrity inspired design to disentangle what household members do in managing their privacy, their privacy practices.